Analisis Preferensi Konsumen Pada Minyak Goreng Kemasan (Studi Kasus Di Kecamatan Purbolinggo Lampung Timur) - Eny Ivan’s; Novita (Jurnal Prodi Agribisnis, 2022)
This study aims to determine the attributes that consumers consider in buying cooking oil. The research was conducted in Purbolinggo District, East Lampung. The number of samples was 100 people who were taken randomly from the population of Purbolinggo District. The method used to determine consumer preferences for packaged cooking oil used nonparametric statistical analysis, namely Chi-Square. Based on the results of the study, it was found that the attributes that were significant as consumer preferences were the brand with the bimoli category, the price in the Rp 23.000-Rp 25.000 category, the size in the 2 liter category, the type of packaging in the refill category, purchase intensity in the indeterminate category, the number of purchases in the category 1 pcs, and clarity with clear category.